PENGARUH KERUSAKAN DAN KELERENGAN JALAN HUTAN TERHADAP PRODUKTIVITAS PENGANGKUTAN KAYU STUDI KASUS DI KALIMANTAN BARAT - S Sutopo; Rahardjo S Suparto (Jurnal Penelitian Hasil Hutan, 1988)
Timber transportation   productivity  decreases  when  forest  road  is  deteriorated   and  the  8lope  is large. This  study tried  to  investigate  the  effect  of  slope  and road  damage  on  timber  transportation  productivity,  and was carried out at the PT Sari Bumi  Kusuma  forest  company   areas in  West Kalimantan in  1987.The  investigation   results are as follows:Slope difference of  5% has significant   effect  on  transportation  productivity.  On  flat,   medium   and  steep  slopes, the productivities  are 265,   219 and  132  m3.  km/hr,   respectively.Transportation   productivity  is significantly influenced   by  a difference  of  15% damage  on  the  road. Productivities on  relatively   good  road, medium damaged  and  badly  damaged  roads  are  292,213  and  136 m3.km/hr, respectively.On flat  and  badly  damaged  roads  (at a damage  level greater  than  30%),   transportation  productivity  is reduced  64% which  caused  significant   financial  loss.  The  allowable  road damage  on  (at  terrain  without   causing financial  loss is 40%.On  medium   terrain  and  medium   damaged  roads  (at  damage  levels  between 15% and  30%), the  loss is significant. Medium damaged  (between 15%  and  30%) and heavy  damaged roads (greater than 30%) caused  transportation productivities  to  be decreased  as much as 25% and 58%,  respectively,   The allowable  road damage on medium   terrain without   causing financial  loss is 26%.On steep  terrain,   transportation   productivity is decreased  significantly i.e. 58% of  those on medium  damaged  roads (between   15% and  30%).  A  maximum   road damage  of  18%  is allowable  without  causing financial  loss.There  is  a significanf   interaction   between  slope  and road  damage.  The  steeper  the  slope  and  the  heavier  the  road damage,  the  larger  the  decrease in  transportation   productivity.In  the  transportation   distance of 60 km  and  the  timber  price  of  US$ 70/m3,  if timber  transportation  productivity decreases 30%,  it is strongly  suggested  to  repair damaged  road  immediatly   in order  to prevent   financial  losses.